PENGARUH KEJELASAN SASARAN ANGGARAN, PENGENDALIAN AKUNTANSI, DAN SISTEM PELAPORAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH KABUPATEN JOMBANG - DIAH PRECELINA, DEVIKA; WURYANI, ENI (Jurnal Akuntansi AKUNESA, 2019)
This study aims to examine the effect of budget goal clarity, accounting control, and reporting systems on the accountability of Jombang Local Government Performance. One hundred questionnaires were distributed directly to the heads of finance, head of accounting, and staff of Jombang Local Government as research respondents. The research uses quantitative methods that are processed with SEMPLS3.The results of this research show that the budget goal clarity and accounting controls has a positive effects on performance accountability, while the reporting system has a negative effect on performance accountability of Jombang Government.